2003
DOI: 10.1136/heart.89.8.875
|View full text |Cite
|
Sign up to set email alerts
|

Normal values of B type natriuretic peptide in infants, children, and adolescents

Abstract: Objective: To determine normal values of plasma B type natriuretic peptide from infancy to adolescence using a commercially available rapid assay. Setting: Tertiary referral centre. Design: The study was cross sectional. Plasma BNP concentration was measured in 195 healthy infants, children, and adolescents from birth to 17.6 years using the triage BNP assay (a fluorescence immunoassay). Results: During the first week of life, the mean (SD) plasma concentration of BNP in newborn infants decreased significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
192
7
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(219 citation statements)
references
References 30 publications
14
192
7
6
Order By: Relevance
“…N values in previous studies have been far too small to reliably define reference intervals for males and females at each age group [8][9][10][11][12][13]. Our data differs from that reported by Rauh et al [13] and Koch et al [26]. While both these papers show higher values for BNP and/or NT-proBNP in neonates and agree with our findings in this regard, their values appear to decline fairly rapidly with increasing age.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…N values in previous studies have been far too small to reliably define reference intervals for males and females at each age group [8][9][10][11][12][13]. Our data differs from that reported by Rauh et al [13] and Koch et al [26]. While both these papers show higher values for BNP and/or NT-proBNP in neonates and agree with our findings in this regard, their values appear to decline fairly rapidly with increasing age.…”
Section: Discussionsupporting
confidence: 65%
“…Another possible reason is the possibility of peptide clearance by the placenta which ends at birth [27]. A close examination of their [13,26] data reveals that the number of male and female children studied at any one age group are very small with numbers of 1 to 6. This would question the reliability of their reference intervals.…”
Section: Discussionmentioning
confidence: 99%
“…19 Previous studies showed that plasma concentration of BNP is high in the first few days after birth due to changes in circulatory volume leading to increased ventricular volume and pressure load. 27,28 In this study, it is suggested that the peak of plasma NT-proBNP level was in the first 48 h of life and then declined rapidly within the first 7 days, except for those with HsPDA in which NT-proBNP levels were approximately 5-8 times higher. Our findings suggest that physiological changes of NT-proBNP follow the pattern of BNP changes.…”
Section: Discussionmentioning
confidence: 68%
“…[20][21][22][23] Studies in adults have shown that NT-proBNP is a more sensitive and more specific marker for ventricular dysfunction than the biologically active BNP. 24,25 Previous studies in healthy full-term infants showed that the plasma BNP level rapidly rises after birth, reaching its peak at day 2-3 of life [26][27][28] and a high plasma BNP level correlates with HsPDA. A decline of BNP level is noted after PDA is closed by indomethacin.…”
Section: Introductionmentioning
confidence: 99%
“…According to age-and sex-specific reference values [11,12], BNP was increased in only 13/67 patients.…”
Section: Resultsmentioning
confidence: 92%